Social Stigma Related to COVID-19 Disease Described by Primary and Secondary School Teachers and Adolescents Living With HIV in Western Kenya - Chory, Ashley; Nyandiko, Winstone; Ashimosi, Celestine; Aluoch, Josephine; Martin, Roxanne; Biegon, Whitney; Munyoro, Dennis; Apondi, Edith; Vreeman, Rachel (Frontiers in Public Health, 2021)
Introduction: Understanding community members' knowledge, attitudes, and beliefs about the novel SARS-CoV-2 virus and the prevalence of associated stigma are critical steps for increasing accurate public health knowledge, encouraging uptake of preventative or mitigating health behaviors, and ultimately bringing the COVID-19 pandemic under control. Methods: We conducted a one-time, phone-based assessment to assess the presence of perceived COVID-19 community stigma reported by Kenyan primary and secondary school teachers, as well as adolescents living with HIV. Participants were previously enrolled in an ongoing, cluster-randomized trial to evaluate the impact of multi-media teacher training on teachers' negative attitudes and beliefs around HIV. The SAFI Stigma Questionnaire, a validated tool to assess HIV-related stigma in this setting, was adapted to ask questions regarding the stigma and discrimination experienced or perceived during the COVID-19 pandemic. Results: We enrolled 330 participants in this study, including 311 primary and secondary teachers (56% female, average age 36 years) and 19 adolescents living with HIV (57.89% female, average age 16.37 years). None of the adolescent participants reported witnessing or experiencing discrimination related to COVID-19, nor did they report losing financial and/or social support. In contrast, the teacher participants reported prominent social stigma experiences of various levels and related to COVID-19. Teachers in the intervention group, who had completed the multi-media training on HIV-related stigma, were significantly less likely to think that the community viewed COVID-19 as a dirty or shameful disease, and less likely to feel it was important to keep their COVID-19 infection a secret, compared to the teacher control group. Conclusion: These findings suggest that COVID-19-related stigma may be prevalent in western Kenya and that interventions to reduce community-level stigma for HIV may also have a protective impact on other stigmatized infectious diseases such as COVID-19.